Characterization of polyhydroxyalkanoates produced by Synechocystis salina from digestate supernatant - Kovalcik, Adriana; Meixner, Katharina; Mihalic, Matthias; Zeilinger, Wolfgang; Fritz, Ines; Fuchs, Werner; Kucharczyk, Pavel; Stelzer, Franz; Drosg, Bernhard (International journal of biological macromolecules, 2017)
The current commercial production of polyhydroxyalkanoates (PHA) is based on heterotrophic bacteria, using organic carbon sources from crops. To avoid the competition with food and feed production, cyanobacteria, metabolising PHA from carbon dioxide can be used. This research focuses on the investigation of the thermal and rheological properties of PHA polymers accumulated by Synechocystis salina, which had been cultivated in digestate supernatant and a mineral medium. The dried bacterial cells had a polymer content of 5.5-6.6%. The relevance of the derived PHA polymers for the common melt polymer processing was correlated with their molecular mass distribution as well as with their thermal and rheological properties. The determined thermal and rheological properties showed that PHA polymers accumulated by S. salina on digestate supernatant or mineral medium are comparable with the commercial available poly(3-hydroxybutyrate). However, the results showed that PHA polymers in general require modification before melt processing to increase their stability in the molten state.
Keywords: molekulová hmotnost; kultivační média; oxid uhličitý; Synechocystis; Synechocystis salina; Carbon Dioxide; Digestate; polyhydroxyalkanoáty; Culture Media; Polyhydroxyalkanoates; Molecular Weight